FREQUENCY OF MALARIAL RECURRENCE IN THE PAEDIATRIC DEPARTMENT OF LYARI GENERAL HOSPITAL KARACHI - RUMAISA, .; NAWAZ, R; FATIMA, S; REHMAN , A; USMAN, A (Biological and Clinical Sciences Research Journal, 2024)
Malaria remains a significant health burden, especially in pediatric populations, with recurrence posing a substantial challenge. Plasmodium vivax is the predominant species responsible for recurrent malaria episodes. Understanding recurrence rates and associated factors is crucial for designing effective interventions to minimize the disease burden in endemic regions. Objective: To determine the recurrence rate of malaria and associated factors in children aged 2-12 years at the Pediatric Department of Sindh Government Lyari General Hospital, Karachi. Methods: A cross-sectional study was conducted over six months. A sample size of 95 was calculated using Open Epi, based on a 9.78% recurrence rate with a 95% confidence interval and a 7% margin of error. Non-probability consecutive sampling was used. Children aged 2-12 years diagnosed with malaria were included, and those with life-threatening comorbidities were excluded. Demographic data, presenting complaints, and clinical findings were recorded. Malaria diagnosis and Plasmodium species identification were confirmed through blood film microscopy, and treatment adherence was observed. Follow-up for recurrence was conducted over three months, with data analysis performed using SPSS Version 25. Results: The mean age of participants was 6.8 ± 2.5 years, with 52% male and 48% female. Common symptoms included fever (90%), chills (75%), and sweating (68%). Plasmodium vivax was identified in 70% of cases, P. falciparum in 25%, and mixed infections in 5%. The total recurrence rate was 10%, primarily due to P. vivax (60%), with recurrences observed across the three follow-up months. Higher recurrence rates were noted in younger children (2-5 years) and those with non-adherence to the treatment protocol (11%). Conclusion: It is concluded that malaria recurrence in children, particularly in those aged 2-5 years, is a notable issue, with Plasmodium vivax being the predominant species in recurrent cases. High adherence to treatment protocols may help reduce recurrence, while targeted follow-up in high-risk groups could improve outcomes.